FILMES FINOS DE COBRE/ÓXIDO DE COBRE COMO AGENTES INIBIDORES DA ADESÃO DE BIOFILMES BACTERIANOS - Scheidt, Gabriele (2013)
This work consisted of modifying the surface of commercial glass using copper/copper oxide thin films to obtain bactericidal properties, that is, a thin film that showed a decrease in bacterial contamination either by bactericidal characteristics or inhibition of biofilm adhesion. The methodology used for film synthesis requires a certain time at elevated pressures at a temperature below the glass transition temperature (Tg). The conditions for thin film synthesis were the temperature of 320° C at constant pressure of 3 MPa during 32 h. The thin films were characterized by the techniques of X-ray diffraction and scanning electron microscopy. For biological assays, the bacteria Acinetobacter sp. was used by a standard method of immersion in Luria Broth with stages of dilution and cultured in a Petri dish, by a process of dripping broth on the surface of that blades, followed by Gram staining. The methodology of growth in broth did not allowed to evaluate the efficiency of thin film copper/copper oxide as bacteriological agent. This result is probably due to the dilution of biocidal particles in relation to the volume of the liquid culture media; consequently, a reduction in the bioactivity was observed. On the other hand, tests on slides showed that bacterial films did not adhere to the surface with copper thin films, as compared to slides without, showing effectiveness in combating biofilm adhesion that are considered one of the major means of bacterial contamination.